Solusi Manajemen Order Menggunakan Metode TOPSIS dan Kanban Board berbasis Android - Abdussalam Mustajib; Friska Narulita, Luvia (Yayasan Nuraini Ibrahim Mandiri, 2024)
Order management is a very crucial process, especially in companies engaged in services. One example is MSMEs engaged in tailor or sewing services. Many problems are faced by MSMEs engaged in tailor or sewing services, especially delays and difficulties in sharing information. Based on the problems experienced by several tailor or sewing service MSMEs, a mobile application was developed to overcome order management which is considered less than optimal. The development will use the Laravel and Flutter frameworks, and will use the Rapid Application Development method because it is considered optimal for small-scale application development. The application will use the kanban board method to facilitate order management, and the TOPSIS method to rank order processing.